2022
DOI: 10.1128/spectrum.01289-22
|View full text |Cite
|
Sign up to set email alerts
|

Acinetobacter baumannii Sampled from Cattle and Pigs Represent Novel Clones

Abstract: Over the last decades, huge amounts of information have been obtained for clinical isolates of A. baumannii and the clones they belong to. In contrast, very little is known about the genomic identity and the genomic basis for virulence and resistance of animal isolates.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 24 publications
(26 reference statements)
0
12
0
Order By: Relevance
“…Supporting this scenario, a 2022 genomic epidemiology paper has shown that cattle and pig isolates belong to novel clones that are not found in humans. 4 Furthermore, some other animals (eg, donkey, goat, and goose) have clones of A baumannii that have not been described in clinical settings. 3 , 5 Another theory could be that animal and human A baumannii populations are not differentiated from one another and exhibit frequent gene flow between both populations.…”
mentioning
confidence: 99%
“…Supporting this scenario, a 2022 genomic epidemiology paper has shown that cattle and pig isolates belong to novel clones that are not found in humans. 4 Furthermore, some other animals (eg, donkey, goat, and goose) have clones of A baumannii that have not been described in clinical settings. 3 , 5 Another theory could be that animal and human A baumannii populations are not differentiated from one another and exhibit frequent gene flow between both populations.…”
mentioning
confidence: 99%
“…However, our results indicate that these interventions can also have negative consequences, since the dysbiosis produced by these drugs could facilitate pathogen colonization, with the consequent higher risk of infection. In fact, we detected in piglets from treated sows some potentials pathogens such as Acinetobacter [72,73], Clostridium [74] or Treponema [75] that were not found in the farm samples. In good health status farms, the colonization of these pathogens is probably controlled by the exclusion provided by the normal nasal microbiota.…”
Section: Discussionmentioning
confidence: 80%
“…A. baumannii has been mainly studied as a hospital-associated organism since its emergence as a nosocomial pathogen in the 1970s. Nonetheless, over the last two decades, studies have shown that these bacteria can be isolated from non-clinical settings [4][5][6][7][8][9]. Yet, many of these studies have focused on animal or animal-related products and a lack of effort is evident in plant and soil environments.…”
Section: Discussionmentioning
confidence: 99%
“…A very recent study even found A. baumannii in a milk tank [11]. Clearly, isolates of this pathogen have been found in different types of environments [4,6,7,9,12]. However, to the best of our knowledge, soil and related plant environments have received little attention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation